Methods of test for sodium tripolyphosphate (pentasodium triphosphate) and sodium pyrophosphate (tetrasodium pyrophosphate) for industrial use. Estimation of tripolyphosphate (triphosphate) content of sodium tripolyphosphate Part 7, (7th June 1974) - British Standards Institution,
No abstract available